2021
DOI: 10.1101/gr.274639.120
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype diversity and sequence heterogeneity of human telomeres

Abstract: Service Email Alerting click here. top right corner of the article or Receive free email alerts when new articles cite this article -sign up in the box at the object identifier (DOIs) and date of initial publication.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 36 publications
5
29
1
Order By: Relevance
“…Similar to several other studies [16, 9], our results showed that the telomeres and centromeres in the human genome are major sources of genetic variation. The combination of long-read technology and the T2T-CHM13 reference genome will likely open up new doors for population-scale studies on roles these satellite sequences to human health and disease [17].…”
Section: Discussionsupporting
confidence: 91%
“…Similar to several other studies [16, 9], our results showed that the telomeres and centromeres in the human genome are major sources of genetic variation. The combination of long-read technology and the T2T-CHM13 reference genome will likely open up new doors for population-scale studies on roles these satellite sequences to human health and disease [17].…”
Section: Discussionsupporting
confidence: 91%
“…It is interesting to note that telomere-like sequences are also frequently found near telomeric regions [19][20][21][22]. Specifically, there are three main types of telomere-like repeat sequences that are frequently found near telomeres in the human genome, namely the c-type repeats (TCA GGG ) n , g-type repeats (TGA GGG ) n, and , j-type repeats (TTG GGG ) n [23].…”
Section: Resultsmentioning
confidence: 99%
“…Telomere length measurement by nanopore sequencing will allow the telomere field to study new questions and revisit past unanswered questions in telomere biology. A different method of long-read sequencing, Pacific Biosciences (PacBio) sequencing, has recently been applied to human telomere sequences, (Grigorev et al 2021) indicating longread sequencing technologies are widely useful in telomere research. It will be of interest to determine whether chromosome end-specific telomere length differences are generalizable to other organisms, as well as perhaps even humans, and understanding how they are established and maintained will be a fascinating new area of telomere biology to explore.…”
Section: Discussionmentioning
confidence: 99%